Kinematics of Supination and Pronation with Stewart Platform - Şenay Baydaş; Bülent Karakaş (Journal of Mathematical Sciences and Modelling, 2021)
This paper presents kinematics form of pronation and supination movement. The algorithm of Stewart platform motion can be used to create a new motion of supination (or pronation) motion. Pronation motion can be taken as Stewart motion which has not any rotation on x-axis and y-axis. In this case, pronation motion has only one parameter. Supination movement creates a helix curve. Additionally, the correlation between rotation angle and extension is 1. This allows us to use artificial intelligence in pronation motion. In this article, the algorithm and Matlab applications of pronation motion are given in the concepts of artificial intelligence approach. This is a new and important approach.